Healthcare utilization and costs of singaporean youth with symptoms of depression and anxiety: results from a 2022 web panel - Parth Chodavadia; Irene Teo; Daniel Poremski; Daniel Shuen Shung Fung; Eric A. Finkelstein (Child and Adolescent Psychiatry and Mental Health, 2023)
Abstract Background There is evidence that the prevalence of depression and anxiety among youth is increasing and that these factors contribute to high healthcare costs and poor school performance. The goal of this study is to provide up-to-date estimates of the prevalence and economic burden of depression and anxiety among youth in Singapore. Methods Using an existing web panel, 991 parents filled out the PHQ-4 screener on behalf of 1,515 youth. 104 of these parents whose children (ages 4 to 21) had symptoms consistent with depression or anxiety filled out a full survey with questions on mental health symptoms, school absences, school performance, and healthcare utilization. The survey was fielded between April and June 2022. Publicly available prices were used to estimate the cost associated with the observed rates of health service use. Findings Based on parental responses, 11.7% (95% CI:10.2 − 13.5%) of youth had symptoms consistent with depression and 12.8% (95% CI:11.2 − 14.6%) had symptoms consistent with anxiety. In total, 16.2% (95% CI:14.5 − 18.3%) were reported to have symptoms consistent with at least one of these conditions. These youths missed an average of 190 (95% CI: 126–254) hours of school per year due to their mental health conditions and parents reported that school and daily activities performance was significantly degraded. Per capita annual healthcare costs averaged S$10,250 (95% CI: 7,150–13,350), with 64% of youth receiving emergency or inpatient services. In aggregate, annual costs associated with these conditions were estimated to be S$1.2 billion (95% CI:S$1.1bn – S$1.4bn). Interpretation Even with significant potential for underreporting, these results reveal concerning rates of Singaporean youth with symptoms consistent with depression or anxiety, many of whom remain untreated. Results also reveal the short-term economic burden caused by these symptoms and hint at longer-term consequences resulting from poor school performance. This study should represent a call to action for Singapore to address poor mental health among youth.